(3fUQI GdaJQI hYUQI GdbWQIs - (3YeGO GdOjf GdcGJH , eMeO Hf eMeO Uaj GdOjf Hf fajS GdOjf MGeO Hf Cdg, YeGO GdOjf CHh YHO Gddg,J (B597 (3g` s
(3ChdgG (B:s
(3hHYO , aEfi cfJ ChKQ Cf CLeY cJGHkG ai hRQGA GdOhdI GdSdLbjI, hCcGHQ OhdJgG heGRdJ CacQ MJi JCedJ GdcJGH GdPi Ufag GdhRjQCfhTQhGf Hf NGdO HGdaGQSjI s
(3BNQgG (B:s
(3hajeG CfTCJg ef eMGSf GdCjGe GdfGUQjI caGjI, hdcd ehab Edi gOGg gOGjI Ke cJGH fUQI GdaJQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B453 s
(3eUOQ GbJfGA GdCUd (B:s
(3HGQjS (B(2145) s
Keywords: (3GdJGQjNs